Blood pressure can be controlled with Chronic Disease Management Programs (PROLANIS) - Fitri suciana; Istianna Nurhidayati; Romadhani Tri Purnomo; Agung Tri Wibowo (Media Keperawatan Indonesia)
Hypertension is a major problem in Indonesia; if handled late, it can cause complications. Controlled blood pressure in hypertensive patients can be done through the chronic disease management programs (PROLANIS) launched by the government. PROLANIS activities include consultation, periodic blood pressure measurement, drug administration, education, and PROLANIS exercises. The research design used a cross-sectional approach, and the number of samples used was 36 respondents with hypertension. This study used a total sampling technique that included all patients with hypertension. Data analysis using Kendall's Tau test. The result is a p-value = 0.000 < 0.05, so it can be concluded that there is a relationship between the activeness of participating in Prolanis activities and blood pressure in hypertensive patients. The correlation coefficient, or r value, of 0.791 shows a strong positive correlation. It can be concluded that there is a relationship between the Chronic Disease Management Program (Prolanis) and the activeness of participating in Prolanis activities with blood pressure in hypertensive patients at the Public Health Center.